Sexually transmitted diseases in a general practice - Hiscock, E. (1982)
A pilot study of the occurrence of latent sexually transmitted diseases in a sexually active sample was carried out in a general practice. The conclusions confirm that a reliable diagnosis of a sexually transmitted disease cannot be made in general practice when based only on the opinion of the patient. Full venereological history, examination and microbiological backup are essential. The microbiological investigations should be broad-based and should not rely on one specimen or method.